Program to reduce work absenteeism in assembly companies developed at the TECNM Campus Fresnillo: Programa de reducción de ausentismo laboral en empresas ensambladoras desarrollado en el TECNM Campus Fresnillo - Reyes Sánchez, José de Jesús; García Camacho, Mario Alberto; Guerrero Vega, Martha Alicia (LATAM Revista Latinoamericana de Ciencias Sociales y Humanidades, 2023)
Absenteeism from work is a very common phenomenon that the Aptiv ll company goes through. It is an expense for the company that the work assigned to a given position is not being carried out by the person who is paid for it when they are absent. Since someone else does the work when a person is absent, this generates a lot of money loss since you have to talk to employees outside the shift to cover the positions of the workers who do not attend, in addition to sometimes it is necessary interrupting the production of the plant due to this social phenomenon, among the main causes are: labor-related reasons such as low salaries and/or mistreatment, mobility despite the company having transportation, personal and even motivational issues.